Peran Kelembagaan Adat Moloku Kie Raha dalam Mewujudkan Sistem Pemerintahan yang Baik di Maluku Utara - Rumkel, Nam; Syafari, Tri; Yunus, Yahya; APHA, Journal Manager (Jurnal Hukum Adat Indonesia, 2018)
This study aims to examine the institution of Moluku Kei Raha in the Indonesian Government System and the meaning of the Institution of Moloku Kie Raha in Organizing Government. The results of this study indicate that the area named Moloku Kie Raha contained four customary institutions, namely the Sultanate of Ternate, the Sultanate of Tidore, the Sultanate of Bacan and the Sultanate of Jailola. The duties and functions of the customary institutions of Moloku Kie Raha have a very important role in realizing a good governance system that is in line with the meaning contained in the customary institutions. Various meanings in the institution of Moloku Kie Raha such as Alam Ma Kolano in the Sultanate of Ternate who have duties and functions as Mandataris or Heads of State, Kie Ma Kolano in the Sultanate of Tidore with duties and functions that secure and defend all regions within the Confederate state. Jiko Ma Kolano in Jailolo with duties and functions to guard the entire border region, and Dehe Ma Kolano in the Sultanate of Bacan who had the task and function of building the economic system of the Confederate country. The meanings of the customary institutions as social capital are very relevant in realizing a system of good governance especially in North Maluku. The four meanings were studied in depth with the concept of management of the regional government system, especially in North Maluku with the meaning of world bobato and bobato akhirati with the existing institutional structure that has strong and inseparable relevance in realizing the commitment to create a good governance system in North Maluku, namely adopting formal institutions with customary institutions found in Moloku Kie Raha.